Perceived Circular Economy as a Mediator between Green Advertising and Circular Buying Behaviour of Green Products - Chan, Tak Jie; Asmaul Husna, Haris Fadzilah; Mohd Safwan, Ramli; AL Amirul Eimer, Ramdzan Ali (IP Media Sdn. Bhd. & SiMo Excel PLT, 2025)
The circular economy has gained attention as the outcome of Sustainable Development Goals (SDGs), which focus on Responsible Consumption and Production (SDG-12). Although the circular economy is a good initiative to make the environment more sustainable, however, consumers’perceptions of circular products are not always favorable. Therefore, this study aims to examine green advertising on the buying behavior of circular products, mediated by the circular economy. The study utilized Signaling Theory as the underpinning theory. The study applied a quantitative approach by using the survey method. The valid 183 respondents were collected via the purposive sampling technique and analyzed using Partial Least Square Structural Equation Modeling. The findings revealed that green advertising positively impacts circular buying behavior and the perception of circular economy. In addition, the circular economy positively impacts circular buying behavior. The study also found that circular economy mediates between green advertising and circular buying behavior. The study provides insightful implications for circular product businesses to embrace green advertising strategies to attract young consumers. In addition, educational institutions and consumer society should inculcate the concept of circular economy and help enrich knowledge and understanding to achieve the SDGs' goals and contribute to sustainable marketing scholarship. KEYWORDS: Circular economy, Green advertising, Circular buying behavior, Sustainable consumption and production, SDG-12